Deposit Mudarabah Investment Risk Analysis Method Value at Risk (VaR) - Iin Emy Prastiwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study is to understand the risk and return on net return on mudharabah deposits in Islamic banks using the Value at Risk (VaR) approach. The objects in this study are quarterly financial statements of Bank Syariah Mandiri, Bank BRI Syariah, and Muamalat Bank for three years, 2015-2017. The VaR analysis results show that the average risk of mudharabah deposit investment for 3 years in Bank Syariah Mandiri is 2015 at 6.61% and net return -0.53%, in 2016 the risk is 0.14% and net return 3.21 %, in 2017 the risk is 0.17% and net return is 0.32%. BRI Syariah Bank is 2015 at 0.08% and net return of 4.28%, in 2016 the risk is 0.07% and net return 3.77%, in 2017 the risk is 0.08% and net return 42.81% . and Bank Muamalat is 2015 at 0.63% and net return of 0.04%, in 2016 the risk is 0.40% and net return is 0.08%, in 2017 the risk is 0.14% and net return is 0.26%. In addition there are differences in the level of risk and return (net return) in Bank Syariah Mandiri, BRI Syariah, and Muamalat Bank with significant probability (p-value) for the risk level of 0.005 and return (net return) of 0.045. From the risk level and net return for three years, BRI Syariah Bank is a bank that has prospective value. Key Words : VaR, risk, net return, mudharabah deposit